Concentrations and exposure risks of some metals in facial cosmetics in Nigeria. (2016) - Iwegbue, Chukwujindu M.A.; Bassey, Francisca I.; Obi, Grace; Tesi, Godswill O.; Martincigh, Bice S.
Abstract: The concentrations of nine metals (Cd, Pb, Ni, Cr, Co, Cu, Fe, Mn and Zn) were determined in lip sticks, lip glosses, lip balms, eye pencils, eyeliners, eye shadows, blushes, mascaras and face powders. The study was aimed at providing information on the risk associated with human exposure to metals in these facial cosmetic products. The concentrations of metals in the samples were measured by atomic absorption spectrometry after digestion with a mixture of nitric acid, hydrochloric acid and hydrogen peroxide. The mean concentrations of metals in these facial cosmetics ranged from 3.1 to 8.4 μg g −1 Cd, 12–240 μg g −1 Pb, 9.1–44 μg g −1 Cr, 18–288 μg g −1 Ni, 1.6–80 μg g −1 Cu, 7.9–17 μg g −1 Co, 2.3–28 mg g −1 Fe, 12–230 μg g −1 Mn, and from 18 to 320 μg g −1 Zn. The concentrations of Ni, Cr and Co were above the suggested safe limit of 1 μg g −1 for skin protection, while Cd and Pb were above the Canadian specified limits. The systemic exposure dosage (SED) values for these metals obtained from the use of these facial cosmetic products were below their respective provisional tolerable daily intake (PTDI)/or recommended daily intake (RDI) values. The margin of safety values obtained were greater than 100 which indicated that the concentrations of the metals investigated in these facial cosmetics do not present considerable risk to the users except in the case of face powders.